The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s00125-005-1871-7
|View full text |Cite
|
Sign up to set email alerts
|

Marked differences in the IGF system that are associated with migration in comparable populations of Gujaratis living in Sandwell, UK, and Gujarat, India

Abstract: Aims/hypotheses: We previously reported independent links between the IGF system and the development of impaired glucose tolerance and cardiovascular risk. This study tests the hypothesis that the lifestyle change which accompanies population migration, with attendant increases in cardiovascular risk, is reflected by changes in the IGF system. Materials and methods: We compared a specific Gujarati community in Sandwell, UK (n=205), with people still resident in the same villages of origin near Navsari, India (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…SHBG levels were also lower in Pakistani men, in keeping with their poorer insulin sensitivity and greater abdominal adiposity. In a separate cross‐sectional study of two Gujarati populations from the same site of origin (Gujarat, Northwest India), 6 we found marked differences in relation to migration in levels of circulating IGF‐I, IGFBP‐3 and IGFBP‐1. The significant cross‐site differences in individuals from the same extended families suggest that environmental exposure and lifestyle factors profoundly influence IGF‐I bioavailability, with potential implications for the risk of developing diabetes and cardiovascular disease in this population.…”
Section: Introducfionmentioning
confidence: 63%
See 1 more Smart Citation
“…SHBG levels were also lower in Pakistani men, in keeping with their poorer insulin sensitivity and greater abdominal adiposity. In a separate cross‐sectional study of two Gujarati populations from the same site of origin (Gujarat, Northwest India), 6 we found marked differences in relation to migration in levels of circulating IGF‐I, IGFBP‐3 and IGFBP‐1. The significant cross‐site differences in individuals from the same extended families suggest that environmental exposure and lifestyle factors profoundly influence IGF‐I bioavailability, with potential implications for the risk of developing diabetes and cardiovascular disease in this population.…”
Section: Introducfionmentioning
confidence: 63%
“…Twenty‐two per cent of Sandwell participants had migrated to the UK before puberty. The Gujarati men whose androgen levels are reported here are all those of Gujarati origin for whom serum was available for analysis from the Gujarati cross‐sectional sample on which we have reported previously 6 …”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Changes in fat distribution over the life-course appear to differ by ethnicity (29,30). Although a genetic susceptibility may be an obvious explanation for ethnic differences in metabolic and obesity characteristics, and for the different trajectories over the life-course, it is notable that total energy intake is higher compared with British Europeans in largely first-generation Indian Asian migrants to the U.K. (35) and in Indian Asian children in the U.K. (36). Within India, migrants from rural to urban areas also have higher energy intakes compared with those of the rural population (37).…”
Section: Discussionmentioning
confidence: 99%
“…This is associated with greater obesity, ectopic fat distribution, and IR. Further, age-related changes in adverse patterns of IR are more marked in Indian Asian migrant populations compared with Indian Asian nonmigrant populations (35). Such rapid changes in metabolic characteristics are likely to be environmentally rather than genetically driven.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the IGF system differed between three ethnic groups (European, African-Caribbean and Pakistani) and that there were significant modulating effects of dietary carbohydrate, fat and protein intake on IGF concentration [23]. Furthermore, in a recent study comparing a specific Gujarati community in Sandwell, UK, with people residing in the same villages of origin in India [24], we found that the environmental changes that accompany migration to the UK have effects on circulating IGF system components consistent with a predisposition to diabetes and heart disease.…”
Section: Effects Of Diet and Migration On The Igf Systemmentioning
confidence: 70%